Weekend Update: Identity, Culture, Politics and Anthropology since the 1980s: Association for Social Anthropology in Oceania 2016 Distinguished Lecture. Issue 3 (14th November 2016) - Friedman, Jonathan
Abstract : In periods of hegemonic power there is a tendency for indigenous groups to be eradicated, assimilated, or turned into stigmatized minorities. Where hegemony weakens, the process is reversed with groups who were previously suppressed or assimilated reasserting their identities, cultures, and political claims on territorial sovereignty. The two processes are different phases of a historical cycle. The decline of Western hegemony provides a space for the rise of culturally‐based identity movements, such as the Hawaiian and Maori sovereignty movements. Such movements in turn foster the emergence of new elites.